Alone Again: John Zubek and the Troubled History of Sensory Deprivation Research. Issue 4 (27th August 2013) - Raz, Mical
<x xml:space="preserve">Abstract</x> In the 1950s, sensory deprivation research emerged as an influential new field for behavioral science researchers, supported by the intelligence community. Within a few years, deprivation research had become ubiquitous; images of sensory deprivation were invoked to explain a wide range of phenomena, from religious revelations to the very structure of psychoanalysis. Yet within a decade and a half, this field of research became implicated in cases of torture and abuse. This article examines the history of University of Manitoba psychologist John Zubek, who remained one of the final researchers still conducting sensory deprivation research in the 1970s. It raises questions on how might it be possible to successfully and cautiously perform controversial research.